Peyton's four-step approach for teaching complex spinal manipulation techniques – a prospective randomized trial. Issue 1 (December 2016) - Gradl-Dietsch, Gertraud; Lübke, Cavan; Horst, Klemens; Simon, Melanie; Modabber, Ali; Sönmez, Tolga; Münker, Ralf; Nebelung, Sven; Knobe, Matthias
Abstract Background The objectives of this prospective randomized trial were to assess the impact of Peyton's four-step approach on the acquisition of complex psychomotor skills and to examine the influence of gender on learning outcomes. Methods We randomly assigned 95 third to fifth year medical students to an intervention group which received instructions according to Peyton (PG) or a control group, which received conventional teaching (CG). Both groups attended four sessions on the principles of manual therapy and specific manipulative and diagnostic techniques for the spine. We assessed differences in theoretical knowledge (multiple choice (MC) exam) and practical skills (Objective Structured Practical Examination (OSPE)) with respect to type of intervention and gender. Participants took a second OSPE 6 months after completion of the course. Results There were no differences between groups with respect to the MC exam. Students in the PG group scored significantly higher in the OSPE. Gender had no additional impact. Results of the second OSPE showed a significant decline in competency regardless of gender and type of intervention. Conclusions Peyton's approach is superior to standard instruction for teaching complex spinal manipulation skills regardless of gender. Skills retention was equally low for both techniques.